2020
DOI: 10.1016/j.rse.2020.111805
|View full text |Cite
|
Sign up to set email alerts
|

Improved groundwater table and L-band brightness temperature estimates for Northern Hemisphere peatlands using new model physics and SMOS observations in a global data assimilation framework

Abstract: There is an urgent need to include northern peatland hydrology in global Earth system models to better understand land-atmosphere interactions and sensitivities of peatland functions to climate change, and, ultimately, to improve climate change predictions. In this study, we introduced for the first time peatland-specific model physics into an assimilation scheme for L-band brightness temperature (Tb) data from the Soil Moisture Ocean Salinity (SMOS) mission to improve groundwater table estimates. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…Limitations to simulating the fate of peatland carbon First, our results are drawn from only five peatland models, and only four of those models can explicitly simulate permafrost processes. To reduce uncertainty in model projections, a better understanding of the differences among models (i.e., the five models used in this study and models with a specific representation for peatland hydrology [46][47][48][49] ) is needed, and our intercomparison of the five state-of-the-art peatland models represents the first step. Further work involving site-level simulations and comparison with manipulative experiments in the field are also needed.…”
Section: Permafrost Peatlands Versus Non-permafrost Peatlandsmentioning
confidence: 99%
“…Limitations to simulating the fate of peatland carbon First, our results are drawn from only five peatland models, and only four of those models can explicitly simulate permafrost processes. To reduce uncertainty in model projections, a better understanding of the differences among models (i.e., the five models used in this study and models with a specific representation for peatland hydrology [46][47][48][49] ) is needed, and our intercomparison of the five state-of-the-art peatland models represents the first step. Further work involving site-level simulations and comparison with manipulative experiments in the field are also needed.…”
Section: Permafrost Peatlands Versus Non-permafrost Peatlandsmentioning
confidence: 99%
“…Our spatially and temporally continuous 9-km simulations were evaluated against water level and not against θ 5cm , because in situ soil moisture data were not sufficiently available. However, remote sensing allows estimation of θ 5cm , which can be linked to the water level in systems with high water levels like peatlands, where the θ 5cm and water level are strongly coupled (Bechtold et al, 2020;Dadap et al, 2019). Bechtold et al (2020) recently showed that correlation between measured and estimated water level increased after data assimilation of Soil Moisture and Ocean Salinity (SMOS) brightness temperature (Tb) over northern peatlands using PEATCLSM North,Nat .…”
Section: Discussionmentioning
confidence: 99%
“…The TOPMODEL approach used in CLSM is not optimal for peatlands because most of them are virtually flat on a macrotopographic scale of kilometers, and bogs (and to a lesser extent fens) appear hydraulically decoupled from the groundwater hydrology of the rest of the catchment (Bechtold et al, 2019(Bechtold et al, , 2020. This decoupling is either due to impermeable sediments at the peat base or due to accumulated peat that lifted the peat surface (and water level) above the range of the groundwater fluctuations in the underlying aquifer.…”
Section: Original Peatclsm Modulementioning
confidence: 99%
“…In ideal conditions this metric should be equal to unity over the entire study area. The normalized O-F residuals were obtained by normalizing each O-F residual by their simulated (expected) (forecast and observation error) standard deviation and then calculating the time-series standard deviation (Bechtold et al, 2020;Reichle et al, 2019). Third, the time-series standard deviations of the increments (analysisforecast) in SSM and LAI were investigated in order to verify whether those values are small relative to the values of the update state variables.…”
Section: Discussionmentioning
confidence: 99%